The Effect of Smoking and Body Mass Index on The Complication Rate of Alloplastic Breast Reconstruction. (June 2020) - Sadok, N.; Krabbe-Timmerman, I. S.; de Bock, G. H.; Werker, P. M. N.; Jansen, L.
Background and Aims: The aim of this study was to evaluate the effect of smoking and body mass index on the occurrence of complications after alloplastic breast reconstruction. Materials and Methods: A consecutive series of 56 patients treated with immediate or delayed alloplastic breast reconstruction, including six cases combined with latissimus dorsi flap, at three hospitals between 2012 and 2018 were included. Complications were scored and defined according to Clavien–Dindo. To evaluate the impact of smoking, body mass index, and other potential risk factors on the occurrence of any and severe complications, univariate and multivariate logistic regression analyses were applied to estimate odds ratios and 95% confidence intervals. Results: In 56 patients, 22 patients had a complication. As much as 46% of smokers had severe complications compared to 18% of non-smokers. Of patients with body mass index ⩾ 25, 40% had severe complications compared to 10% with body mass index < 25. Smokers had eight times more chance of developing severe complications than non-smokers (ORadjusted  = 8.0, p  = 0.02). Patients with body mass index ⩾ 25 had almost 10 times more severe complications compared to patients with body mass index ⩽ 25 (ORadjusted  = 9.9, p  = 0.009). No other risk factors were significant. Conclusion: Smoking and body mass index ⩾ 25 both increased the complication rate to such an extent that patients should be informed about their increased risk for complications following alloplastic breast reconstruction and on these grounds surgeons may delay alloplastic breast reconstruction. It is an ethical dilemma whether one should deny overweight and obese patients and those who smoke an immediate alloplastic breast reconstruction. For both life style interventions, adequate guidance should be made available.